Effects of Pelvic Floor Muscle Training with Biofeedback in Women with Stress Urinary Incontinence - Araujo, Nazete dos Santos; Nunes, Érica Feio Carneiro; Oliveira, Ediléa Monteiro de; Rodrigues, Cibele Câmara; Janahú, Lila Teixeira de Araújo (IntechOpen, 2012)
None